The Potential of Red Algae Methanol Extract (Kappaphycus alvarezii) as an Antibacterial Agent Toward Pseudomonas aeruginosa and Enterococcus faecalis Bacteria - Novitasari, Nabila; Yulianti, Evy; Mercuriani, Ixora Sartika; Sugiyarto, Lili; Ariyanti, Nur Aeni (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Urinary tract infection (UTI) is a disease caused by both Gram-negative and Gram-positive bacteria. Red algae (Kappaphycus alvarezii) contain bioactive compounds derived from secondary metabolites with antibacterial properties. This study investigates the potential of Kappaphycus alvarezii methanol extract to inhibit the growth of Enterococcus faecalis ATCC 29212 and Pseudomonas aeruginosa ATCC 27853 using the microdilution broth method, determining Minimum Inhibitory Concentration (MIC) values ranging from a concentration of 500 µg/mL to 1.9531 µg/mL. To elucidate the inhibition mechanism, nucleic acid, protein, and Ca2+ ion leakage assay were performed via spectrophotometry at MIC 1, MIC 2, and MIC 3 concentrations. Morphological changes in the bacterial cell membrane were further examined using Scanning Electron Microscopy (SEM) at MIC 2. The results demonstrated that, the methanol extract of K. alvarezii exhibited significant antibacterial activity against Enterococcus faecalis bacteria with an MIC value of 1.9531 µg/mL, but showed no inhibitory effect on Pseudomonas aeruginosa. The extract inducted membrane leakage, as indicated by a higher leakage value compared to negative controls and commercial antibiotics. In addition, the methanol extract of K. alvarezii caused alterations in bacterial cells. These findings highlight the potential of Kappaphycus alvarezii methanol extract as a promising antibacterial agent.